Poverty and Digital Divide: A Study in Urban Poor Neighborhoods - Tri Mulyaningsih; Rutiana Wahyunengseh; Sri Hastjarjo (Jurnal Ilmu Sosial dan Ilmu Politik, 2020)
Literature suggests that the penetration of digital technology may create a digital divide, particularly for groups that lack resources and the capacity to access technology. This study is keen to examine the poverty and digital divide, particularly in urban poor areas. There are two research objectives. Firstly, to examine the digital diffusion and digital literacy within poor urban neighborhoods in the City of Magelang, Central Java, Indonesia. Secondly, to understand the variation of digital diffusion and digital literacy across areas (with different levels of poverty), age groups, genders and occupations. The data is collected from surveys focused on measuring the access to information, digital diffusion and the use of technology among the poor. This study found that there is a digital divide problem among people in urban areas, especially among people with low incomes. Moreover, the diffusion is dominated by certain groups such as younger people and females. Furthermore, digital literacy among the poor is low. The policy implication is to improve access for digital diffusion and provide assistance to improve digital literacy skills.